Globalization, Language, and Culture: Reflections on Appadurai’s Perspectives (Spandan, 2023)
Globalization, as a multifaceted phenomenon, influences culture, language, and human interaction on a global scale. This article reflects on Appadurai's theoretical perspectives on globalization, particularly his concepts of disjuncture and 'scapes.' Appadurai critiques the homogenization narrative, emphasizing how global cultural flows like ethnoscapes, technoscapes, mediascapes, financescapes, and ideoscapes shape 'imagined worlds' and cultural identities. These 'scapes' depict the interconnected yet disjunctive realities of globalization, fostering cultural hybridization and deterritorialization. Ethnoscapes illustrate global mobility, while technoscapes and financescapes signify the technological and financial dynamics across borders. Mediascapes and ideoscapes highlight the global dissemination of media and ideologies. The paper also examines how these flows challenge conventional notions of cultural imperialism, proposing an understanding of globalization's cultural impact. By reflecting on Appadurai's insights, this study contributes to the ongoing discourse on globalization's implications for cultural diversity and identity.